The experience of disseminating quality culture between systemic aspects and value elements - Mion, Laura; Bruno, Raimondo (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2024)
Quality culture can be considered a specific type of organisational culture, which concerns a set of values and objectives related to quality. The aspects that determine it can be divided into two categories: the first linked to systemic aspects of the organisation, the second, on the other hand, concerning a more cultural sphere, which concerns value factors. Starting from a framework of quality culture, consisting of a number of theoretical indicators outlined through a phenomenological analysis, the aim of this research is to investigate the degree of dissemination of these indicators within the specific context of an Italian university. The analysis also takes into account the different perceptions of the subjects based on whether or not they have a specific position within the governance or evaluation system. A further objective of the research is to verify the validity of the tool used, in order to grasp any potential for development and further use in the national panorama. The analysis of the data revealed the need for a quality culture to incorporate a focus on both internal and external stakeholders through the active involvement of students and external recognition. In addition, alongside a general maturity of the tools and procedures of the quality system, a great need emerged for action to simplify them. In order to exercise greater autonomy in implementing and pursuing its vision of quality, the university must ...